Comparison of recombinant and plasma-derived antithrombin biodistribution in a rabbit model - Berry, Leslie R.; Thong, Bruce; Chan, Anthony K. C. (Thrombosis and Haemostasis, 2009)
Antithrombin (AT) is a native plasma protein that acts as the main inhibitor of enzymes generated by the coagulation cascade. In extreme thrombotic conditions, consumption of plasma AT can make treatment with AT-associated heparin therapies less effective. Supplementation with recombinant human AT (rhAT) has shown promise but altered pharmacokinetics were observed when comparing stable heparin complexes of the plasma-derived AT (pAT) and rhAT proteins. To understand the differential clearance mechanisms,biodistribution of rhAT and pAT was determined. 125I-labelled ATryn (rhAT) or Kybernin P (pAT) was intravenously injected into rabbits. At various time points, animals were sacrificed and organs analysed for bound radioactivity. 131I-albumin, injected shortly before termination, was used as a marker for trapped blood. Levels of circulating protein + metabolites were significantly less for rhAT than pAT (p < 0.001) and removal of acid soluble fragments confirmed that differences were due to more rapid rhAT clearance. More rhAT (28% dose) than pAT (3% dose) was liver-associated by the earliest time points, corresponding to elevated rhAT degradation products in urine/feces. However, at intermediate times (4 hours), rhAT showed significantly increased arterial and venous uptake over pAT (p ≤0.001).These vessel wall interactions accounted for the primary differences between clearance of rhAT and pAT during these time periods. Overall, circulating rhAT is more rapidly lost to the liver and vessels than pAT. Increased vessel wall binding may facilitate rhAT treatment of vascular thrombosis.
Keywords: Antithrombin; biodistribution; pharmacokinetics; protein glycosylation; vessel wall